Older persons' care as life care : a pastoral assessment of the ecclesia praxis within the African Methodist Episcopal Church in South Africa - Carnow, Jacobus Johannes (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.